Interfacial charge transfer with exfoliated graphene inhibits fibril formation in lysozyme amyloid - Gregory, Wren E. (Biointerphases, 2020)
Amyloid fibrillation is known to contribute in a variety of diseases including neurodegenerative disorders (e.g., Alzheimer's and Parkinson's disease) and type II diabetes. The inhibition of fibrillation has been suggested as a possible therapeutic strategy to prevent neuronal and pancreatic β-cell death associated with amyloid diseases. To this end, strong hydrophobic and π-π interactions between proteins and nanomaterials at the nanobio interface could be used to mitigate the stacking of amyloid structures associated with fibrillation. In this study, the authors show that exfoliated graphene effectively inhibits the formation of amyloid fibrils using a model amyloid-forming protein, viz., hen egg white lysozyme (HEWL). While previous theoretical models posit that hydrophobic and π-π stacking interactions result in strong interactions between graphene and proteins, the authors experimentally identified the presence of additional interfacial charge transfer interactions between HEWL and graphene using micro-Raman spectroscopy and Kelvin probe force microscopy. Their photoluminescence spectroscopy and transmission electron microscopy studies evince that the interfacial charge transfer combined with hydrophobic and π-π stacking interactions, specifically between the nanomaterial and the amino acid tryptophan, increase HEWL adsorption on graphene and thereby inhibit amyloid fibrillation.